The impact of Zoom as a learning application on student learning concentration in the COVID-19 era - Fuad Azhar Makarim El Yusuf; Tasya Susanti (Curricula: Journal of Curriculum Development, 2022)
The presence of COVID-19 has hampered the activities carried out by the community, one of which is in the field of education. With the entry of the era of the Industrial Revolution 4.0, education must follow technological developments and take advantage of technological sophistication to facilitate the learning process. Today there are many technological innovations in the world of education, for example, in the form of applications or learning platforms that can support the learning process between educators and students. This study aims to determine the effect of the ZOOM learning application in the COVID-19 era on students' learning concentration. The study used descriptive quantitative methods with survey activities as data collection, involving students from junior high school, senior high school, vocational school, and university level as respondents. The results showed differences in students' level of concentration during distance learning and face-to-face learning. After participating in distance learning assisted by the ZOOM video conferencing application, the concentration of students decreased to focus on learning. So it can be concluded that the ZOOM application influences the concentration of student learning during the COVID-19 pandemic. It is hoped that increasingly advanced technological developments can help students concentrate on learning.   Abstrak Hadirnya COVID-19 membuat aktivitas yang dikerjakan oleh masyarakat menjadi terhambat, salah satunya di bidang pendidikan. Dengan masuknya era revolusi industri 4.0, ranah pendidikan dituntut harus mengikuti perkembangan teknologi dan memanfaatkan kecanggihan teknologi guna memperlancar proses pembelajaran. Dewasa ini banyak inovasi teknologi dalam dunia pendidikan, contohnya dapat berupa aplikasi atau platform pembelajaran yang dapat mendukung terjadinya proses pembelajaran antara pendidik dan peserta didik. Penelitian ini bertujuan untuk mengetahui pengaruh aplikasi pembelajaran Zoom Meeting di era COVID-19 terhadap konsentrasi belajar siswa. Penelitian menggunakan metode kuantitatif deskriptif dengan kegiatan survei sebagai pengumpulan datanya, dengan melibatkan peserta didik jenjang SMP, SMA, SMK, sampai dengan jenjang perguruan tinggi sebagai responden. Hasil penelitian menunjukkan bahwa terdapat perbedaan tingkat konsentrasi peserta didik saat pembelajaran jarak jauh dengan pembelajaran tatap muka. Setelah mengikuti pembelajaran jarak jauh yang dibantu oleh aplikasi video conference Zoom Meeting, konsentrasi peserta didik mengalami penurunan untuk fokus terhadap pembelajaran. Sehingga dapat disimpulkan bahwa aplikasi ZOOM ini sangat berpengaruh terhadap konsentrasi pembelajaran peserta didik di masa pandemi COVID-19 ini, diharapkan dengan perkembangan teknologi yang semakin maju, dapat membantu konsentrasi siswa terhadap pembelajaran. Kata Kunci: COVID-19; edukasi; E-Learning; video konferensi